Structure of the Electrical Double Layer at the Interface between an Ionic Liquid and Tungsten Oxide in Ion-Gated Transistors - Barbosa, Martin S. [UNESP]; Balke, Nina; Tsai, Wan-Yu; Santato, Clara; Orlandi, Marcelo O. [UNESP] (Amer Chemical Soc, 2020)
The structure of electrical double layers at electrified interfaces is of utmost importance for electrochemical energy storage as well as printable, flexible, and bioelectronic devices, such as ion-gated transistors (IGTs). Here we report a study based on atomic force microscopy force-distance profiling on electrical double layers forming at the interface between the ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and sol-gel films of mesoporous tungsten oxide. We successfully followed, under in operando conditions, the evolution of the arrangement of the ions at the interface with the tungsten oxide films used as channel materials in IGTs. Our work sheds light on the mechanism of operation of IGTs, thus offering the possibility of optimizing their performance.